Babesia microti Protein BmSP44 Is a Novel Protective Antigen in a Mouse Model of Babesiosis - Wang, Hui; Wang, Yao; Huang, Jilei; Xu, Bin; Chen, Junhu; Dai, Jianfeng; Zhou, Xia (Frontiers in Immunology, 2020)
Babesiosis caused by Babesia species imposes an increasing threat to public-health and so far, there is no effective vaccine to prevent Babesia infections. Babesia proteins containing signal peptide are involved in the invasion of erythrocytes. In our previous study, a surface antigen of B. microti merozoites, named as BmSP44 was identified as a dominant reactive antigen by protein microarray screening. To evaluate its potential applications in diagnosis and prevention of Babesiosis, the open reading frame encoding BmSP44 was cloned and the recombinant protein was expressed. In consistent with the protein microarray result, recombinant BmSP44 (rBmSP44) can be recognized by sera from B. microti infected mice. Immunofluorescence assays (IFA) confirmed that BmSP44 is a secreted protein and localized principally in the cytoplasm of the parasites. The parasitemia and Babesia gene copies were lower in mice administered rBmSP44 antisera compared with normal controls. Active immunization with rBmSP44 also afforded protection against B. microti infection. The concentrations of hemoglobin in rBmSP44 immunization group were higher than that in the control group. Importantly, vaccination of mice with rBmSP44 resulted in a Th1/Th2 mixed immune response with significantly elevated IL-10 and IFN-ɣ levels during the early stage of infection. Taken together, our results indicated that rBmSP44 can induce a protective immune response against Babesia infection. Thus, BmSP44 can be used as both a diagnosis marker and a vaccine candidate.